Learning Program of National Vision Cultivation to Indonesian Children with Permanent Resident Status - Izzati, Khoerul Izzati; Adiarti, Wulan (BELIA: Early Childhood Education Papers, 2020)
Many conflicts that arise in Indonesia such as loss of humanity, love and respect for NKRI, recognition of the culture by other nations, causing division between regions, countries and nations. Therefore, it becomes an important thing to cultivate learning national vision into the nation's next-generation, especially from an early age. Various character values ​​need to be applied to children, especially the character to love culture of the nation and country, which is grown through learning the cultivation of national vision. So, children know the origin of their birth and various cultures of their resident people. This study aims to determine the learning program for the cultivation of national vision in Indonesian children with permanent resident status (PR) at Little Stars Kindergarten, School of Indonesia (Singapore) Ltd. In addition, this study aims to see how the behavior of students after participating in the learning of national vision at Little Stars Kindergarten, School of Indonesia (Singapore) Ltd. The target of this study is Indonesian children with permanent resident (PR) status, aged 4-6 years at Little Stars Kindergarten, School of Indonesia (Singapore) Ltd. This study uses qualitative methods, with data collection through observation, interviews and documentation (triangulation). Permanent Resident is the legal status granted by a country so that it has the same position as a citizen. Almost all students at SIS Little Stars are permanent residents. The results of this study indicated that students with permanent residency (PR) status at Little Stars Kindergarten, Indonesia School (Singapore) Ltd, have diverse national perspectives. The national vision possessed by students includes: knowing the city or country of origin at birth, local languages, special foods, Indonesian national songs, some folk songs, and general knowledge about Indonesian culture. Students still have a national vision for Indonesian, even though they have long-lived and settled in Singapore. This is the output of the learning of national vision conducted by the teacher.